As narrativas míticas da comunidade quilombola de Morrinhos/Poconé/MT e os fazeres escolares - Campos, Jocimar Jesus de (2017)
This investigation is linked to the Postgraduate Program at the Master’s level of the Universidade Federal de Mato Grosso and the research line: Movimentos Sociais, Política e Educação Popular. This study aimed to comprehend the relationships among narratives and shared memories in the quilombola community of Morrinhos/Poconé/MT with the knowing and doings of the Escola Municipal Professora Catarina Antônia da Silva. In this proposal, it was made the historical, identity and cultural characterizations, after that, were described the mythical narratives that pervade the community and simultaneously to comprehend the didactical materials, the Pedagogical Political Plan and pedagogical practices considered in those narratives. In that route, it was used the ethnographic method offered by Geertz (2008) and the oral historical genre of Holanda e Meihy (2014). Theoretically, this investigation also was based on the contributions of Bosi (2015), Benjamin (1990), Castilho (2011), Hampaté Bâ (2010), Halbwachs (1990), Munanga (2005), Vansina (2010) and some others. The main collection instruments of findings were: the interviews, participant observation and documentary analyses. In the interviews, it was used the semi-structured questionnaire. The dialogues made possible the memories and experiences recovery of old men and women of the community. In this sense, the participant observation provided the researcher, the daily accompaniment of the knowing and doings in the community and described it in a meticulous and dense way relevant to religiosity, the relationship with the environment and the pedagogical practices. The content analysis was supported by Bardin (1995), in the sense of collating the data collected from the narratives, the Pedagogical Political Plan and the didactic book used by the school. In this context, the participants of the investigation were: four old men and women, one professor and four students. The results pointed out the social function importance performed by the old men and women in the quilombola community of Morrinhos, considering that they hold the lived experience and are the support of the group. Over all, they are the guardians of the spontaneous educative messages and/ or the natural ones that permeate in the cultural universe of the community. Through that bias, the mythical legends emphasize messages to the children and young people, such as the respect to the nature and the obedience for the old ones, for that reason, they are valorized and constitute the relevant cultural capital to the community. In that way, they are precious literary sources to be recognized by the school in its curriculum giving origin to a counterpoint, the Eurocentric narratives that still prevail in the actions and school practices of that community.